2000
DOI: 10.1089/10799900050116426
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Ovulatory Cycle on Cytokine Production: Evaluation of Systemic, Cervicovaginal, and Salivary Compartments

Abstract: To understand the impact of the menstrual cycle on immunologic parameters, we measured the level of cytokines and chemokines from plasma, cervicovaginal lavage (CVL), and saliva samples of 6 premenopausal women during the follicular and luteal phases of the ovulatory cycle. We demonstrate that the level of plasma interleukin-8 (IL-8) was 4-fold higher during the follicular phase than the luteal phase (p = 0.004), whereas plasma IL-1beta, IL-4, IL-6, IL-10, interferon-gamma (IFN-gamma), transforming growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
58
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 23 publications
7
58
0
1
Order By: Relevance
“…20 Secretion of mannosebinding lectin, a molecule in the complement system that plays a critical role in host protection, from vaginal epithelial cells is increased in the LUT phase of the menstrual cycle. 49 Other investigations found that CV immune mediators did not change based on the menstrual cycle (e.g., IL-10, TNF-a, IL-8, RANTES, and TNFR II), 19,26,50 but were higher during menstruation. 26,50 Genital tract cytokines have also been shown to vary based on clinical factors, such as cervical ectopy, inflammation, and sexual activity.…”
Section: No Significant Differences In Vaginal Immune Cells Between Fmentioning
confidence: 97%
See 3 more Smart Citations
“…20 Secretion of mannosebinding lectin, a molecule in the complement system that plays a critical role in host protection, from vaginal epithelial cells is increased in the LUT phase of the menstrual cycle. 49 Other investigations found that CV immune mediators did not change based on the menstrual cycle (e.g., IL-10, TNF-a, IL-8, RANTES, and TNFR II), 19,26,50 but were higher during menstruation. 26,50 Genital tract cytokines have also been shown to vary based on clinical factors, such as cervical ectopy, inflammation, and sexual activity.…”
Section: No Significant Differences In Vaginal Immune Cells Between Fmentioning
confidence: 97%
“…45 No significant differences in the antimicrobial activity of the CVL The secretion of cervical mucus is significantly influenced by endogenous reproductive hormones, with cervical mucus volume peaking with surges in preovulatory serum E2. [46][47][48] The biologic rationale for differences in antimicrobial activity of the CVL is based on data from small cohorts showing that secreted cytokines, chemokines, and other cationic antimicrobial polypeptides in the vagina have significant alterations in concentrations based on the phase of the menstrual cycle with immune factors such as IL-6, IL-1b, IL-1RA, and MIP-1b being significantly higher in the FOL phase versus the LUT phase, 19,27 while IL-1a and b-defensin were significantly elevated in the LUT phase. 27 Keller et al found that immune mediators, SLPI, a and b defensins, lysozyme, and lactoferrin, were significantly lower at mid-cycle ovulation compared with both the FOL and LUT phases.…”
Section: No Significant Differences In Vaginal Immune Cells Between Fmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Th1 cytokine production by PBMCs in response to trophoblast extracts was not influenced by when in the menstrual cycle the study samples were obtained (Hill JA, unpublished results), which is consistent with relevant data from other published reports, 31 although the levels of IL-4 produced by PBMCs and IL-1 and IL-8 in serum may vary between the two phases of the menstrual cycle. [31][32][33] Therefore, Th1 immunity to trophoblast, which is associated with IL1B polymorphism in women with RPL, appears to be a specific memory immune response. To our knowledge, ours is the first study demonstrating that polymorphisms of a cytokine gene, IL1B are associated with Th1 immunity to trophoblast in women with RPL.…”
mentioning
confidence: 99%